(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Cleft lip and cleft palate are common congenital craniofacial anomalies requiring timely multidisciplinary care, yet access to treatment remains limited in many low- and middle-income settings due to social and structural barriers. Methods: This study employed a mixed-method services study purposively selected 105 treated and untreated adult patients with a craniofacial anomaly. Data were collected from September 2019 to June 2023. Socio-demographic data were collected utilizing the world health Study on global ageing and adult health (SAGE) survey. A questionnaire was used to assess the socio-cultural, economic, and healthcare barriers including stigmas. The qualitative component included in-depth interviews with 16 patients and 7 key informants involved in cleft services. Samples were obtained from the Department of Orthodontics, Faculty of Dentistry at Bangladesh Medical University, National Institute of Burn and Plastic Surgery, and Bangladesh Specialised Hospital, Dhaka, Bangladesh. Results: Fear of unnecessary tests (67.6%), inability to visit the doctor regularly (65.7%), long waiting times (62.0%) and fear of not getting treatment from the same physician (61%) were the most commonly reported barriers. Social and familial stigma (70.3%) and financial hardships (50.6%) were the commonly found socio-cultural and socio-economic barriers. The major personal factors for receiving healthcare were work responsibilities and transportation (96.2% each) and fear for personal safety (53.3%). The qualitative findings support the above results. Conclusion: Perceived fear of caring out undergoing unnecessary investigation by the patients, socio-cultural stigma, economic constraints, and health system limitations continue to hinder access to cleft lip and palate treatment in Bangladesh. Overcoming these barriers is therefore essential to promote equitable access and improve health outcomes for affected individuals.